2014
DOI: 10.1136/bmjopen-2014-005047
|View full text |Cite
|
Sign up to set email alerts
|

Use of probiotics to correct dysbiosis of normal microbiota following disease or disruptive events: a systematic review

Abstract: ObjectiveTo assess the evidence for the claim probiotics can correct dysbiosis of the normal microbiota resulting from disease or disruptive events.SettingSystematic review of published clinical trials of patients receiving a probiotic intervention for the prevention or treatment of various diseases.Data sourcesSources searched (1985–2013): PubMed, EMBASE, Cochrane Database of Systematic Reviews, CINAHL, AMED and ISI Web of Science. Three on-line clinical trial registries were searched: Cochrane Central Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(133 citation statements)
references
References 112 publications
1
120
0
5
Order By: Relevance
“…A systematic review of the data available on the use of probiotics in a clinical context showed that the probiotics with the greatest ability to restore the microbiota have the strongest clinical efficacy 174 . As the gut microbiota is a complex network of species interacting with the host, such a restoration could be accomplished by acting on single or multiple nodes of the network, at a compositional and/or at a functional level 175 .…”
Section: Microbiome Geneticsmentioning
confidence: 99%
“…A systematic review of the data available on the use of probiotics in a clinical context showed that the probiotics with the greatest ability to restore the microbiota have the strongest clinical efficacy 174 . As the gut microbiota is a complex network of species interacting with the host, such a restoration could be accomplished by acting on single or multiple nodes of the network, at a compositional and/or at a functional level 175 .…”
Section: Microbiome Geneticsmentioning
confidence: 99%
“…Moreover, probiotics are used as adjuvant treatment for many diseases that affect the GI tract, such as diarrhea, inflammatory bowel disease (IBD), cancer, Helicobacter pylori infection, vaginosis, allergy, and lactose intolerance (Hill et al, 2014;McFarland, 2014;Narbona Lopez et al, 2014;Williams, 2010). The mechanisms through which probiotic bacteria alter the progression of liver diseases are thought to relate to modifications in the composition of the natural intestinal microbiota and its activity.…”
Section: Mechanisms Of Action Of Probiotics In Liver Diseasesmentioning
confidence: 99%
“…Likewise, it is accepted that probiotic s generally have a short-term beneficial effect on the gut microbiota [88, 89], promoting growth of other beneficial microbes, and facilitating host immune response. Members of the lactic acid bacteria (LAB) group including several species of lactobacilli are commonly regarded as probiotics.…”
Section: Advancements In Gut Microbiome Modulation and Host Healthmentioning
confidence: 99%
“…L. rhamnosus also has an effect on host gene expression and immune response, activating nuclear factor-κB (NF-κB), protein kinase C, and phosphoinositide 3-kinase (PI3K) pathways [91, 92]. Probiotics including species of Bifidobacterium, Lactobacillus, and Saccharomyces are regularly administered as interventions to correct dysbioses caused by disease, chemotherapy or other drug treatments [89]. By understanding the molecular mechanisms by which probiotic microbes modulate the gut microbiota through a combination of NGS and microbiology approaches, it becomes possible to develop tailored microbial interventions to treat or prevent specific chronic and acute gastrointestinal diseases.…”
Section: Advancements In Gut Microbiome Modulation and Host Healthmentioning
confidence: 99%